Liver Expression of Sulphotransferase 2A1 Enzyme Is Impaired in Patients with Primary Sclerosing Cholangitis: Lack of the Response to Enhanced Expression of PXR - Ewa Wunsch; Marta Klak; Urszula Wasik; Malgorzata Milkiewicz; Malgorzata Blatkiewicz; Elzbieta Urasinska; Olivier Barbier; Dariusz Bielicki; Dimitrios P. Bogdanos; Elwyn Elias; Piotr Milkiewicz (Journal of Immunology Research)
Background/Aim. Sulphotransferase 2A1 (SULT2A1) exerts hepatoprotective effects. Transcription of SULT2A1 gene is induced by pregnane-X-receptor (PXR) and can be repressed by miR-378a-5p. We studied the PXR/SULT2A1 axis in chronic cholestatic conditions: primary sclerosing cholangitis (PSC) and primary biliary cirrhosis (PBC). Materials/Methods. Western-blot/PCRs for SULT2A1/PXR were performed in PSC (n=11), PBC (n=19), and control liver tissues (n=19). PXR and SULT2A1 mRNA was analyzed in intestinal tissues from 22 PSC patients. Genomic DNA was isolated from blood of PSC patients (n=120) and an equal number of healthy volunteers. Liver miRNA expression was evaluated using Affymetrix-Gene-Chip miRNA4.0. Results. Increased PXR protein was observed in both PSC and PBC compared to controls and was accompanied by a significant increase of SULT2A1 in PBC but not in PSC. Decreased expression of SULT2A1 mRNA was also seen in ileum of patients with PSC. Unlike PBC, miRNA analysis in PSC has shown a substantial increase in liver miR-378a-5p. Conclusions. PSC is characterized by disease-specific impairment of SULT2A1 expression following PXR activation, a phenomenon which is not noted in PBC, and may account for the impaired hepatoprotection in PSC. miRNA analysis suggests that SULT2A1 expression in PSC may be regulated by miR-378a-5p, connoting its pathogenic role.